1978
DOI: 10.1002/j.1551-8833.1978.tb04198.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Technology to Meet the interim Primary Drinking Water Regulations for Inorganics: Part 2

Abstract: This second article of a series outlines specific treatment technology for arsenic and selenium removal from potable water. The first article, which appeared in the February 1978 issue of the JOURNAL, discussed fluoride and nitrate removal. Subsequent articles will review the treatment technology for the six other NIPDWR‐regulated inorganic contaminants and the radionuclides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…The ferric sulfate achieved better removal than the alum (88.6%-99.0% versus 18.5%-93.6%) and was less sensitive to increases in pH. Sorg and Logsdon [15] reported comparable findings in their pilot-scale study-i.e., significant removal of arsenic with conventional treatment and superior performance by the ferric coagulant. Similar results are also cited from an earlier bench-scale evaluation conducted by Logsdon et al [16].…”
Section: Introductionmentioning
confidence: 84%
“…The ferric sulfate achieved better removal than the alum (88.6%-99.0% versus 18.5%-93.6%) and was less sensitive to increases in pH. Sorg and Logsdon [15] reported comparable findings in their pilot-scale study-i.e., significant removal of arsenic with conventional treatment and superior performance by the ferric coagulant. Similar results are also cited from an earlier bench-scale evaluation conducted by Logsdon et al [16].…”
Section: Introductionmentioning
confidence: 84%
“…Hossain (2006) reported that the UNICEF is going to use some improved field test kits like Arsenator, kit with photometer (developed by Mahidol University in Thailand), and kit based on the molybdenum blue method which does not produce arsine gas (Hussam et al, 1999;Christen, 2001). Sorg and Logsdon (1974) reviewed arsenic removal technologies intensively. The most commonly used As removal methods are oxidation, co-precipitation and adsorption onto coagulated flocs, lime treatment, adsorption onto sorptive media, ion exchange resin and membrane techniques (Hering et al, 1996(Hering et al, , 1997Joshi and Chaudhuri, 1996).…”
Section: Testing Proceduresmentioning
confidence: 99%
“…These include pre-formed iron (hydr)oxides (Pierce & Moore, 1982;Goldberg, 1986;Waychunas et al, 1993;Fuller et al, 1993;Fendorf et al, 1997;Grossl et al, 1997;Raven et al, 1998;Manning et al, 1998;Jain et al, 1999) and coprecipitation with ferric and ferrous salts Roberts et al, 2004;Sorg & Logsdon, 1978). Zero-valent iron (ZVI) filings have also been effective at removing arsenic compounds from water (Su & Puls, 2001;Lackovic et al, 2000;Bang et al, 2005b,a), presumably due to adsorption onto iron corrosion products.…”
Section: Review Of Arsenic Adsorption Literaturementioning
confidence: 99%